PENGARUH PEMBERIAN REWARD DAN PUNISHMENT TERHADAP MOTIVASI BELAJAR IPA SISWA SDN 33 SANANE - Aspar Aspar; Muh Yahya; Eka Apriyanti (Universitas Muhammadiyah Purwokerto, 2022)
Reward and Punishment are one of the components that must be deceived by teachers in every learning activity so that student learning motivation is higher. The type of research used is quantitative research with a correlative descriptive approach. The sample used probability sampling so that the sample was 22 students in class V. The data collection techniques used are questionnaires and observations. The data analysis techniques used are inferential analysis and hypothesis testing. The results showed that there was a significant influence on the three variables both initially and simultaneously.